The Effect of Service Quality on Customer Satisfaction in the Airline Industry in Tanzania - Parsaoran Hinsa Pardede, Davy (Green Publisher Indonesia, 2024)
Background: The development of airlines owned or managed by private parties today shows a fairly high development so that the level of competition to get customers is increasingly difficult. One of the strategies carried out by airline management is to provide optimal service, it is expected that those who provide flight services will meet the expectations of their customers, able to win the competition which ultimately gets maximum profit. Purpose: This study is intended to determine the results of service quality on the satisfaction of Airline clients in Tanzania, especially Precision Air Limited customers Method: The explanatory study designed the data collected using interview method of 4oo customers of Precision Air Limited, non-probability sampling procedure was used to select a sample of respondents from the target population, multiple regression analysis to answer the research objectives. Key information in the study was collected through questionnaires, interviews, and observations. Pearson correlation was carried out to assess the strength and direction of linear relationships between variables, multiple regression models at a significance level of 5% were used to determine the relationship between dimensions of service quality and customer satisfaction Results: The results in this study show that the findings spread that the five spheres of facility excellence are positively related to customer satisfaction. Relying on multiple regression results, it was found that the significance value of each independent variable was tangible 0.674, reliability 0.001, assurance 0.449, and empathy 0.000 Conclusion: It can be concluded that service quality is seen from three dimensions: dependability, receptiveness, understanding have a positive and significant effect on client satisfaction. Two dimensions: tangibility and guarantee as part of it have a positive effect but do not have a significant effect on customer satisfaction of Precision Air Limited.